Occurrence, distribution and molecular analysis of Fusarium head blight on cereals in Northeast Algeria - Belgacem, Alaeddine; Mebarkia, Abdelkrim (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Fusarium head blight (FHB) affects cereals by reducing yield quality and quantity. This study aimed, on the one hand, to evaluate the prevalence, severity, and incidence of this disease on durum wheat and barley fields in the High Setifian Plains Region Northeast of Algeria and, on the other hand, to identify Fusarium species. Durum wheat and barley fields were prospected, and FHB-symptomatic samples were collected during two crop years (2018-2019). The prevalence, incidence, and severity results on durum wheat during the first crop year were 6 %, 12.1 %, and 56.2 %, and on barley, were 23.77 %, 10.22 %, and 49.7 %, respectively. However, in the second crop year, on wheat were 2.5%, 3 %, and 35 %, and on barley were 35 %, 10.86 %, and 44.29 %, respectively. Morphological characterization was used to select the 102 isolates. They were then identified by molecular analysis by PCR amplification and sequencing of the internal transcribed spacers (ITS) and β-tubulin (tub2) or translation elongation factor 1-alpha (tef1). Thus, seven species of Fusarium were identified, namely, F. equiseti (27.45 %), F. graminearum (25.49 %), F. acuminatum (19.6 %), F. oxysporum (13.73 %), F. proliferatum (9.8 %), F. avenaceum (1.96 %), F. incarnatum (1.96 %). In addition, Fusarium proliferatum and F. oxysporum were reported for the first time in Algerian fields.